Existence and uniqueness of a solution for a two dimensional nonlinear inverse diffusion problem - Abtahi, M.; Pourgholi, R.; Shidfar, A. (Nonlinear analysis, 2011)
The problem of identifying the coefficient in a square porous medium is considered. It is shown that under certain conditions of data f,g, and for a properly specified class A of admissible coefficients, there exists at least one a∈A such that (a,u) is a solution of the corresponding inverse problem.